History of cold weather tests, Ladd Field Alaska, winter 1947-48. (March Air Force Base (Calif.) : U.S. Air Force, 94th Fighter Squadron, 1st Fighter Group, 1949)
This report contains a complete analytical accounting of the 94th Fighter Squadron's participation in Cold Weather Test at Ladd Field, Alaska, during the winter of 1947-48. Includes planning, deployment, personnel, equipment, and operations.